IDENTIFIKASI JENIS JAMUR PATOGEN UNTUK PENGENDALIAN RAYAP TANAH Coptotermes sp. (PERENNIAL, 2010)
Fungi have a great diversity and wide distribution at the world. It can be used as the alternative technology for controlling of subterranean termite attack, particularly genus Coptotermes knowned as the wooden destructive organism, by using entomophatogenic fungi. For the purpose of the study, several isolate sources were taken from some locations. The results show that eight numbers of pathogenic fungi was founded by screening and identification of fungi taken from 19 numbers of isolate sources. The pathogenic fungi were Beauveria sp., Penicillium brevicompactum, P. rubrum, Paecilomyces fulvus, Fusarium verticolloides, Pythium sp., and Aspergillus sp.Key words: Jamur entomopatogen, Coptotermes sp.